BAHASA INDONESIA RAGAM HUKUM - Simon Sabon Ola (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2009)
The legal register of Bahasa Indonesia has some characteristics indicating its register nature. The characteristics of the register are : (1) normative, and also manipulative, (2) logics, (3) argumentative, and (4) specific typical diction, or word choice. The normative implies to rule the society to do something and not to do something else. This gives a space to “manipulate” the language to deviate the interpretation. The characteristics of logics and argumentative is the major point of legal register, either in the formulation of a law, or in its implementation. The legal register in Bahasa Indonesia also has typical vocabulary, for example: banding, kasasi, memori banding, pleidoi, novum, and etc.